The Endocannabinoid System as a Target in Cancer Diseases: Are We There Yet? - Moreno, Estefanía; Cavic, Milena; Krivokuca, Ana; Casadó, Vicent; Canela, Enric (Frontiers in Pharmacology, 2019)
The endocannabinoid system has been placed in the anti-cancer spotlight in the last decade. The immense data load published on its dual role in both tumourigenesis and inhibition of tumour growth and metastatic spread has transformed the cannabinoid receptors CB1 (CB1R) and CB2 (CB2R), as well as other members of the endocannabinoid-like system, into attractive new targets for the treatment of various cancer subtypes. Although the clinical use of cannabinoids has been extensively documented in the palliative setting, clinical trials on their application as anti-cancer drugs are still ongoing. As drug repurposing is significantly faster and more economical than de novo introduction of a new drug into the clinic, there is hope that the existing pharmacokinetic and safety data on the endocannabinoid system ligands will contribute to their successful translation into oncological healthcare. CB1R and CB2R belong to the G protein-coupled receptor (GPCR) superfamily of membrane proteins. GPCRs have been found to form homodimers, heterodimers and higher order oligomers with other GPCRs or non-GPCRs. Currently, several CB1R and CB2R-containing heteromers have been reported and, in cancer cells, CB2R form heteromers with the G protein-coupled receptor 55 (GPR55) and the tyrosine kinase receptor (TKR) human V-Erb-B2 Avian Erythroblastic Leukaemia Viral Oncogene Homolog 2 (HER2). These protein complexes possess unique pharmacological and signalling properties, and their modulation might affect the antitumoural activity of the endocannabinoid system. This review will explore the potential of the endocannabinoid network in the anti-cancer setting as well as the clinical and ethical pitfalls behind it, and will develop on the value of cannabinoid receptor heteromers as potential new targets for anti-cancer therapies and as prognostic biomarkers.